Academic Cloud ERP Quality Assessment Model - Kridanto Surendro; Olivia Olivia (Institute of Advanced Engineering and Science, 2016)
In the past few decades, educational institutions have been using conventional academic ERP system to integrate and optimize their business process. In this delivery model, each educational institutions are responsible of their own data, installation, and also maintenance. For some institutions, it might cause not only waste of resources, but also problems in management and financial aspects. Cloud-based Academic ERP, a SaaS-based ERP system, begin to come as a solution with is virtualization technology. It allows institutions to use only the needed ERP resources, without any specific installation, integration, or maintenance needs. As the implementation of Cloud ERP increases, problems arise on how to evaluate this system. Current evaluation approaches are either only evaluating the cloud computing aspects or only evaluating the software quality aspects. This paper proposes an assessment model for Cloud ERP system, considering both software quality characteristics and cloud computing attributes to help strategic decision makers evaluate academic Cloud ERP system.